A Discourse on Brutalism Architecture: The Forgotten Architecture Style in Architecture Revolution - Wahid, Julaihi; Abdullah, Azli; Al Ansi, Nashwan; Titisari, Ema Yunita; Hyder, Afaq C. (RUAS, 2023)
This paper explores the Brutalism architectural style. This style became popular in the 1950-1970s with the start of experimentation with building materials in line with the social movements of that time. This research uses an exploratory approach based on a longitudinal study of similar studies. The discussion focused on the architects' revolutionary thinking towards unique designs through form manipulation and material exploration. The results of his work show the determination of form seekers, material experimentation, and the enthusiasm of young architects for monumental architecture. Massive and unadorned reinforced concrete frames, simplicity, minimal ornamentation, small windows, and rough surfaces are usually used for government buildings, institutions, and high-rise housing. The popularity of Brutalism spread to the Far East. The formation of Brutalist architecture in Malaysia left its mark on the urban landscape, but developed into a combination of architectural compositions in architectural pedagogy.